Pengaruh Job Insecurity, Burnout, Dan Reward Terhadap Turnover Intention Pada CV REQUEL HFS MEDAN - Rini Elvina Br Nababan; Sahat P. Remus Silalahi; Rintan Saragih (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine and analyze the influence of Job Insecurity, Burnout and Reward on Turnover Intention of CV REQUEL HFS Medan employees. The main problem in this study is the high level of employee turnover intentions which is suspected to be triggered by a sense of insecurity in work and high work fatigue. The population in this study were all 40 employees of CV REQUEL HFS Medan. The sampling technique used saturated sampling (census), where all members of the population were sampled. The data analysis method used was multiple linear regression analysis with the help of SPSS software. The results of the study partially showed that Job Insecurity had a positive and significant effect on Turnover Intention with a sig value of 0.021 <0.05, Burnout had a positive and significant effect on Turnover Intention with a sig value of 0.000 <0.05, Reward had no significant effect on Turnover Intention with a sig value of 0.244>0.05. Simultaneously Job Insecurity, Burnout and Reward had a significant effect on Turnover Intention. The coefficient of determination (R2) value shows that 64.3% of the Turnover Intention variable is influenced by the three independent variables, while the remaining 35.7% is explained by other variables outside this study.